Fine genetic mapping and transcriptomic analysis revealed major gene modulating the clear stripe margin pattern of watermelon peel - Yang, Shao; Amanullah, Sikandar; Duan, Yaru; Guo, Yu; Xu, Ming; Bao, Xiuping; An, Bohan; Yuan, Chengzhi; Liu, Xiujie; Liu, Jixiu; Gao, Yue; Zhao, Wen; et al. (Frontiers in Plant Science, 2024)
The peel stripe margin pattern is one of the most important quality traits of watermelon. In this study, two contrasted watermelon lines (slb line (P1) with a clear peel stripe margin pattern and GWAS-38 line (P2) with a blurred peel stripe margin pattern) were crossed, and bi-parental F2 mapping populations were developed. Genetic segregation analysis revealed that a single recessive gene is modulating the main-effect genetic locus (Clcsm) of the clear stripe margin pattern of peel. Bulked segregant-based sequencing analysis (BSA-Seq) and fine genetic mapping exposed the delimited Clcsm locus to a 19.686 kb interval on chromosome 6, and the Cla97C06G126680 gene encoding the MYB transcription factor family was identified. The gene mutation analysis showed that two non-synonymous single nucleotide polymorphism (nsSNP) sites (Chr6:28438793 (A-T) and Chr6:28438845 (A-C)) are contributing to the clear peel stripe margin pattern, and the quantitative real-time polymerase chain reaction (qRT-PCR) also showed a higher expression trend in the slb line than in the GWAS-38 line. Further, the comparative transcriptome analysis identified major differentially expressed genes (DEGs) in three developmental periods (4th, 12th, and 20th days after pollination (DAP)) of both parental lines. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses indicated highly enriched DEGs involved in metabolic processes and catalytic activity. A total of 44 transcription factor families and candidate genes belonging to the ARR-B transcription factor family are believed to regulate the clear strip margin trait of watermelon peel. The gene structure, sequence polymorphism, and expression trends depicted the significant differences in the peel stripe margin pattern of both parent lines. The ClMYB36 gene showed a higher expression trend for regulating the clear peel stripe margin of the slb line, and the ClAPRR5 gene depicted a higher expression for modulating the blurred peel stripe margin in the GWAS-38 line. Overall, our fine genetic mapping and transcriptomic analysis revealed candidate genes differentiating the clear and blurred peel stripes pattern of watermelon fruit.